Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik PT. Berkat Alam Sukses Dengan Metode TOPSIS - Yulius Setiawan; Muhammad Rachmadi (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2023)
A company can develop if within a company there are quality human resources (HR). HR is certainly very important to pay attention to, and be given appreciation for every success or achievement they have gotten. This company is a company engaged in the distribution of building materials in which the selection of the best employees is still done manually. In selecting the best employees for each period, the branch head selects the best employees only based on subjective assessment criteria so that the selection process is less effective. then a Decision Support System for the Selection of the Best Employees will be developed. This system was developed using the Rational Unified Process (RUP) methodology, use case diagrams, class diagrams, activity diagrams, entity relationship diagrams, PHP programming language with Laravel Framework and system development using Visual Studo Code and MySQL as the database. The results of making this Decision Support System can help companies make decisions in selecting the best employees more easily and provide transparent information to employees.